Trim optimizations of an adaptive tailless aircraft with composite wing - Xie, J.; Yang, Z. C.; Guo, Shijun J. (Trans Tech Publications, 2011)
This paper investigates aeroelastic tailoring and optimal trailing edge control surface deflection to minimize induced drag for a HALE UAV flying wing configuration. The analysis process is conducted on the Finite Element(FE) model of a composite slender wing. Genetic Algorithm(GA) is employed to aeroelastically tailor the wing by setting the composite ply orientation. The study examined conformal and traditional flaps and explored two optimization formulations to minimize drag. The impacts of the conformal control surface are recognized as required deflection saving which can be translated to drag reduction. The results also show that the control demands for the optimal trim can be further reduced if the wing is properly tailored
Keywords: Active aeroeiastic wing; Adaptive wing; Aeroeiastic tailoring; Inaucea drag; Trim optimization